Posible efecto de El Niño en el zooplancton no gelatinoso del Golfo Dulce, Pacífico de Costa Rica, 1997-1998 - Quesada-Alpízar, Marco A. (2006)
The possible effect of “El Niño” in the non-gelatinous zooplankton in Golfo Dulce, Pacific coast of Costa Rica during the period of 1997-1998. Non-gelatinous zooplankton was studied in Golfo Dulce, an embayment on the Pacific coast of Costa Rica, during the period 1997-1998. Five sampling stations were selected, representing different areas of the gulf. Previous to each zooplankton sampling, a 2 L Niskin bottle was used to collect water and determine water temperature, salinity, and dissolved oxygen throughout the water column at intervals of 10 m from the surface to a depth of 60-100 m. Temperature variation in the water column was used to locate the thermocline. A conical zooplankton net of 0.50 m in diameter and 153 μm mesh size, with a remote closing device in its mouth was used. Sampling included a vertical haul above the thermocline, one through it, and one below it at each station. Samples were fixed in 4 % formaldehyde. Later, a fraction was separated using a Folsom plankton splitter. In average, zooplankton abundance was 3 793 ± 4 867 ind/m3, with a significantly higher abundance in the upper layer of all stations (F= 66.7, p <0.05). The station with the highest abundance in the upper layer was GD-03 (n= 9 921 ±8 334 ind/m3). The mid layer showed relatively low densities, ranging between 1 585 ± 759 ind/m3 and 2 626 ± 3 102 ind/m3. The deep layer was relatively poor in zooplankton, with values that varied between 946 ± 1 069 ind/m3 and 1 307 ± 1 270 ind/m3. In general, the most abundant group during the study period was the copepods (71.47 %), followed by appendicularians (8.25 %), ostracods (7.99 %), invertebrate eggs (5.43 %), polychaete larvae (1.8 %), and chaetognaths (1.03 %). Cluster analysis indicated that the inner stations behaved differently from outer stations. The possible impact of the El Niño on the distribution, composition and abundance of the non-gelatinous zooplankton is discussed. Rev. Biol. Trop. 54 (Suppl. 1): 225-240. Epub 2006 Sept. 30.